Remote sensing monitoring of vegetation and analysis of carbon storage changes in Fengshan Park, Jiaozuo - Erwen ZHENG; Zhe LI; Ping WANG; Zhonghao JIN; Libo NING (Shuiwen dizhi gongcheng dizhi)
Global climate change has attracted much attention to the study of ecosystem carbon storage, with vegetation carbon estimation after mine restoration emerging as a critical component for evaluating ecological restoration effectiveness and supporting the development of a “dual-carbon society”. Traditional methods for estimating vegetation carbon storage have limitations, while advances in remote sensing technology offer promising alternatives. The fractured mountain park in Jiaozuo City has caused serious damage to the ecological environment due to non-standard mining activities. Since 2005, the local government has invested in ecological restoration, using engineering models such as hanging net spray seeding and fish-scale pits to plant a large number of trees and shrubs, significantly improving the vegetation cove of the park. Using the GF-1 satellite data with a resolution of 2 m in 2013, 2018 and 2023, combined with the remote sensing and multiple linear regression model, the vegetation index and other characteristic factors were extracted, and the estimation model of carbon storage was constructed and tested. The results showed that the vegetation carbon storage in the park increased significantly from 2013 to 2018, from 1.56×103 t to 1.90×103 t, and slightly decreased to 1.78×103 t from 2018 to 2023. Vegetation carbon storage is affected by slope and human activities. There are differences in vegetation carbon density in different slope ranges. The vegetation carbon density is higher in the 0.46°−8.32° gentle slope area, while the carbon density is relatively low in the 30.45°− 48.82°steep slope area. Vegetation carbon storage is positively correlated with vegetation coverage, and the change trend was consistent. The research fills the gap in the study of vegetation carbon storage in urban parks transformed from abandoned mines, and provides scientific basis and data support for the evaluation of mine ecological restoration effects and the construction of local “dual-carbon society”.